Analisis Pengaruh Sudut Kemiringan Terhadap Daya Keluaran Pada Panel Surya Jenis Polycrystalline 100 WP Menggunakan Regression Quadratic - Hardianto, muhammad andre; Putri, Novia Utami; Pranita, Elka; Dalimunthe, Ernando Rizki (Institut Teknologi Dirgantara Adisutjipto, 2025)
This research discusses how to find a suitable tilt angle for use on POLYCRYSTALLINE 100 WP solar panels using quadratic regression from 08.00-16.00 with a tilt angle ranging from 0° to 60°. In this researcher, the quadratic regression method is used to find predicted values which will later be compared with the slope angles which have the closest values between the field data and the predicted data. Based on the research results obtained, it shows that the optimal tilt angle is 5.11° with an average power produced of 66.51 watts/hour and an RMSE value from a tilt angle of 0° to 60° of 3. Meanwhile, the average energy produced was issued based on a tilt angle of 5.11° of 13.6 watts/hour with an overall RMSE value from an angle of 0° to 60° of 7.52